Implementation of Economy Civics Through Citizen Participation in Urban Farming Program - Fajar Sidiq Muttaqin; Endang Danial; Prayoga Bestari (Jurnal Civicus, 2022)
This research is motivated by the problem of the city of Bandung which has a dependence on the food sector in the surrounding area. In order to overcome this problem, the Bandung City government created an Urban Farming program by involving the community to contribute to the implementation of the program. Urban Farming is the program carried out by problems. The results obtained from urban farming in these cities have an impact not only on food problems, but also benefits in the economic sector. This aspect of economic benefits is the focus of research using a qualitative approach with a case study method that was carried out in Pajajaran Village, Bandung City with sources consisting of the Food and Agriculture Office of Bandung City, Pajajaran Village Officials, and the Community. This research data collection through interviews, observations, and documentation studies with data analysis techniques in the form of data reduction, data presentation, conclusions, and data validation. The results obtained from this study indicate that the participation of citizens in the Urban Farming program is a form of the implementation of the economy civics through the produced are selling value as well as an impact on the community economy and food security City